DIVISION OF LAND SERVICES BASED ON LOCAL GOVERNMENT AUTHORITY - Sri Winarsi; Sri Hajati; Oemar Moechthar (Jurnal Dinamika Hukum, 2018)
After the issuance of Law Number 23 Year 2014 jo. Law Number 9 Year 2015 on Regional Government, the affairs of local government in the field of land services, especially agriculture and plantations have shifted the authority of regulation which is different from the regulation in Law Number 32 Year 2004. The presence of the regional autonomy-based regulation had established the land agency in the provinces, districts/municipalities which were given authority to hold land affairs. Land affairs was originally the authority of the National Land Agency. These developments cause problems including overlapping authority. If the conflict is not well regulated, in legal perspective, it will emerge the problem of legal uncertainty while in management perspective, it causes inefficiency. Due to the shifting of this land affairs basis, it is necessary to harmonize the land affairs related to regional autonomy so that the authority overlapping is not done simultaneously between the central government and local government. The method used in this research is statute, conceptual and case approach. The research concluded to propose a model of improving land services in agriculture and plantation sectors between central and local government. Keywords: conflict of authority, land service, local government.